An integrated model for the delivery of IT content in an accounting curriculum - Godfrey, RAJ; Tam, T (School of Accounting, Royal Melbourne Institute of Technology (RMIT), 2012)
Rapid advances in information technology (IT) have produced significant changes to the ways in which businesses are operated. Accountants are involved in wide-ranging roles in business and it is important for them to possess IT knowledge and skills relevant to their roles to provide competent and professional services. This raises the questions: What kind of IT knowledge and skills do accountants need? What are the entry-level IT skills and knowledge that accounting educators should provide? The objective of the research is to produce a holistic set of IT knowledge and skills relevant to accounting graduates and to develop a model for the delivery of IT content in an accounting curriculum. The study identified 18 IT topics for accounting graduates categorised into varying degrees of importance. The findings of this study also led to the development of a model for delivery of IT content named as the INDUCTION-DIFFUSION-ASSIMILATION model.
Keywords: Accounting curriculum; Accounting education; Graduate employability; IT knowledge and skills for accountants; IT content delivery; Delphi method